UGV-UAV Integration Advancements for Coordinated Missions: A Review - Shahar, Farah Syazwani; Sultan, Mohamed Tariq Hameed; Nowakowski, Marek; Łukaszewicz, Andrzej (Springer Nature, 2025)
The integration of Unmanned Ground Vehicles (UGVs) and Unmanned Aerial Vehicles (UAVs) represents a transformative leap in autonomous system coordination, combining ground mobility with aerial flexibility to tackle complex real-world missions. However, disparities in communication protocols, sensor interoperability, and autonomy frameworks pose persistent integration challenges. This review critically analyzes these gaps by synthesizing current literature and field practices. It introduces a novel Unified Robotic Protocol (URP) that enables real-time communication between ROS- and MAVLink-based systems, secured via blockchain technology. AI-driven swarm intelligence and modular payload systems are also proposed to enhance decentralized task allocation and operational adaptability. Key findings show significant improvements in system interoperability, mission coordination, and resilience under real-world constraints. This paper concludes with a roadmap for advancing secure, interoperable, and intelligent multi-agent systems.